2019
DOI: 10.1523/jneurosci.2248-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Quantitative Genetic Analysis of Cerebral Surface Area in Youth

Abstract: The genetics of cortical arealization in youth is not well understood. In this study, we use a genetically informative sample of 677 typically developing children and adolescents (mean age 12.72 years), high-resolution MRI, and quantitative genetic methodology to address several fundamental questions on the genetics of cerebral surface area. We estimate that Ͼ85% of the phenotypic variance in total brain surface area in youth is attributable to additive genetic factors. We also observed pronounced regional var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 60 publications
6
14
0
Order By: Relevance
“…Although the similarity between twin pairs in the sizes of V1, V2, and V3 is not explained by similarity in total cortical area, the total cortical area is in fact highly similar between twin pairs. Notably, the correlation for the full cortical surface is substantially higher than that for any other region and is substantially higher in MZ twins (rICC = 0.93) than in DZ twins (rICC = 0.73), consistent with prior reports showing high heritability of cortical surface area (Panizzon et al, 2009;Winkler et al, 2010;Gomez-Robles et al, 2015;Schmitt et al, 2019) (Fig. 8E).…”
Section: The Size Of Retinotopic Maps Is Similar Between Twin Pairssupporting
confidence: 89%
“…Although the similarity between twin pairs in the sizes of V1, V2, and V3 is not explained by similarity in total cortical area, the total cortical area is in fact highly similar between twin pairs. Notably, the correlation for the full cortical surface is substantially higher than that for any other region and is substantially higher in MZ twins (rICC = 0.93) than in DZ twins (rICC = 0.73), consistent with prior reports showing high heritability of cortical surface area (Panizzon et al, 2009;Winkler et al, 2010;Gomez-Robles et al, 2015;Schmitt et al, 2019) (Fig. 8E).…”
Section: The Size Of Retinotopic Maps Is Similar Between Twin Pairssupporting
confidence: 89%
“…A recent study, however, in children reported that at age 9 there was no significant relationship between intelligence and cortical thickness, but at age 12 a negative correlation between intelligence and thickness across the cortex was observed 16 . Conversely, cortical area has been shown to be positively associated with intelligence scores in adolescents 17 . Both thickness and area have been shown to be genetically correlated with intelligence in children and adolescents 16,17 .…”
Section: Introductionmentioning
confidence: 97%
“…Conversely, cortical area has been shown to be positively associated with intelligence scores in adolescents 17 . Both thickness and area have been shown to be genetically correlated with intelligence in children and adolescents 16,17 . These findings suggest that brain morphology is related to intelligence and that the two share a common genetic basis.…”
Section: Introductionmentioning
confidence: 97%
“…Since the advent of the spin test, numerous neuroimaging experiments have adopted it to corroborate claims about intermodal similarities (Lefèvre et al 2018;Paquola et al 2019;Schmitt et al 2019;Shafiei et al 2020;Cui et al 2020;Stoecklein et al 2020) and have extended its implementation to regionally parcellated maps (Váša et al 2018;Vázquez-Rodríguez et al 2019;Cornblath et al 2020).…”
Section: Introductionmentioning
confidence: 99%